Groups and Organization of Political Islam during the president Mohammad Anwar Al- Sadat 28 September 1970- 6 October 1981 - Youssef, Khalat; Al-Butani, Abdul Fattah; Muhammad, Sherzad (Humanities Journal of University of Zakho, 2020)
The interpretations differed in analyzing the significance of sectarian sedition events in Egypt's modern history. However, the ruling authority bears a big amount of responsibility about stressing the atmospheres and provoking sectarian sedition, because the president Sadat resorted to enter into political alliances and combine the power of the church with political Islam.He played on all ropes with all sides. At the time that the Coptic Church noticed that the regime allied whit the political Islam in order to achieve some of its political goals which raised their deep concern about the continuation of that policy and the effects of discrimination against them. In other side political Islam groups had seen that the regime aligned whit the church especially procrastination in the application of Islamic law, while the regime had seen that the both sides the church and the political Islam are elements of threatening the security and political destabilization. The authority did not hesitate in exercising that policy to contain the political conflicts with sound logic and finding exchange trust between them, which has lost its political correctness largely and the inability of the authority to maintain a balance between the two sides with political skillful and wisdom. This ultimately mode both sides rivals to the government as well as ideological conflict between the both sides, which led to escalating tensions and consequently violent clashes.